2004
DOI: 10.4049/jimmunol.173.5.3250
|View full text |Cite
|
Sign up to set email alerts
|

Targeted Deletion of Protein Kinase C λ Reveals a Distribution of Functions between the Two Atypical Protein Kinase C Isoforms

Abstract: Protein kinase C λ (PKCλ) is an atypical member of the PKC family of serine/threonine kinases with high similarity to the other atypical family member, PKCζ. This similarity has made it difficult to determine specific roles for the individual atypical isoforms. Both PKCλ and PKCζ have been implicated in the signal transduction, initiated by mediators of innate immunity, that culminates in the activation of MAPKs and NF-κB. In addition, work from invertebrates shows that atypical PKC molecules play a role in em… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
67
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 86 publications
(79 citation statements)
references
References 61 publications
(55 reference statements)
12
67
0
Order By: Relevance
“…The actin cytoskeleton is a dynamic element within cells that undergoes changes that are essential to cell motility (Lambrechts et al, 2004). PKCi depletion resulted in the formation of long actin stress fibers; similar changes in stress fibers were described by Soloff et al (2004), in PKCi knockout mouse embryonic fibroblasts) and other studies have also implicated the atypical protein kinase C family in stress fiber loss (Uberall et al, 1999;Coghlan et al, 2000).…”
Section: Discussionmentioning
confidence: 60%
“…The actin cytoskeleton is a dynamic element within cells that undergoes changes that are essential to cell motility (Lambrechts et al, 2004). PKCi depletion resulted in the formation of long actin stress fibers; similar changes in stress fibers were described by Soloff et al (2004), in PKCi knockout mouse embryonic fibroblasts) and other studies have also implicated the atypical protein kinase C family in stress fiber loss (Uberall et al, 1999;Coghlan et al, 2000).…”
Section: Discussionmentioning
confidence: 60%
“…Whereas PKC / Ϫ/Ϫ mice are embryonic lethal (46), PKC Ϫ/Ϫ mice are grossly normal, but exhibit an impairment of IKK activation in whole lung extracts after LPS challenge (33). In freshly isolated AM from PKC Ϫ/Ϫ mice, however, NF-B activation was apparent both basal and LPS induced.…”
Section: Pkc Is Essential For Sp-a-mediated I B-␣ Stabilization and Imentioning
confidence: 98%
“…Genetic deletion studies in mice have demonstrated an essential role for aPKCλ during early mammalian embryogenesis, as all aPKCλ -/-mice are embryonic lethal (Soloff et al, 2004). Homozygous aPKCζ -/-mice, however, show normal embryogenesis, suggesting that aPKCλ may compensate for loss of aPKCζ within those embryos (Leitges et al, 2001).…”
Section: Redundant and Compensatory Function Of Apkc ζ For Apkc λ Durmentioning
confidence: 99%